Parametrização do albedo e correção da temperatura da superfície no balanço de energia por imagens Landsat 8 na transição Cerrado-Pantanal - Angelini, Lucas Peres (2018)
The surface energy balance is one of the most important biophysical processes in environmental studies and has been estimated by remote sensing techniques. However, with the operation of new orbital sensors as OLI some parameters need parameterizations to estimate the energy balance. Therefore, the objective of this research was to evaluate the effects of parameterized albedo and corrected surface temperature on the energy balance and evapotranspiration by Landsat 8 satellite images in a Cerrado-Pantanal transition region. The study area covers the CerradoPantanal transition region in the south of the State of Mato Grosso. We used images from the Landsat 8 satellites OLI and TIRS sensors and MODIS MOD09A1 product images between the years of 2013 to 2016, obtained from the USGS ESPA platform. The parameterized surface albedo model was developed from a multiple linear regression in which the surface albedo proposed by Liang (2000) was used as reference. Four algorithms were used to correct the atmospheric effects applied to the brightness temperature. The albedo, surface temperature and brightness temperature estimates were inserted in the SEBAL algorithm, which was validated by measurements and estimates of the energy balance by the Bowen ratio method. The parameterized albedo model obtained better performance in all the uses of the sampled soil with decrease of the errors in relation to the conventional model. The brightness temperature was significantly lower than the surface temperatures. There were no significant differences between the surface temperatures estimated by the models. The net radiation estimated by the parameterized albedo was smaller and had smaller errors. The values of sensible flux, latent flux and evapotranspiration estimated by the parameterized albedo had smaller errors. The obtained results show that the surface albedo exerts a greater impact on the energy balance and evapotranspiration estimates than the surface temperature correction.